Comparison of biopsychosocial functioning of women of different nationalities in the perimenopausal period - Makara-Studzińska, Marta; Kryś-Noszczyk, Karolina Maria; Wdowiak, Artur; Kamińska, Marzena; Bakalczuk, Szymon; Bakalczuk, Grzegorz (Menopause Review/Przegląd Menopauzalny, 2014)
Introduction : The perimenopausal age is a time of many changes in women’s health. Changes in women’s health affect all spheres of life, because health is not merely the absence of disease or infirmity but full psychological, physical and social well-being. Presentation and comparison of the biopsychosocial functioning of women of different races and nationalities in perimenopause, identification of the most common menopause symptoms occurring among women and their needs. Material and methods : Work supported with research examples. Using the PubMed database, the medical literature was searched for works that contain the key words menopause and race or ethnicity published between 1996 and 2013 and available in English. Literature in Polish is a supplementary issue. Results : Various demographic processes taking place in the countries of Africa, North and South America, Asia and Europe are the basis for observing the situation in perimenopausal women in these countries. Caucasian women living in North America and Europe most often experience the negative symptoms of menopause, hindering daily functioning, and women living in urbanized countries in Asia best assess their health condition, both psychosocial and physical. Conclusions : Biopsychosocial functioning of women varies among countries. Developing countries should be given the necessary support and financial information to ensure the health and quality of life in perimenopausal women. In most countries of the world there has been observed the need to promote women’s health, particularly research aimed at prevention, increasing physical activity and attention to nutrition.